Is Good Health Contagious? The Impact of BMI Environment on Individual BMI - Caitlin McKennie; Laura M. Argys; Andrew I. Friedson (Institute of Labor Economics (IZA), 2018)
Increasing trends in obesity have driven policymakers around the US to examine factors associated with lower Body Mass Index (BMI) and improved health. Our research examines the relationship between an individual's health and their environment. Specifically, we examine whether moving to a state with a different statewide average BMI than the state of origin leads to changes in individual BMI. Combining individual data from the 1997 cohort of the National Longitudinal Survey of Youth with state-level data on average BMI from the Centers for Disease Control, we find that individuals experience changes in BMI that move their individual BMI based on the BMI of their destination state relative to their state of origin. The effect is largely due to female moving to states with much higher BMI than their state of origin. These individuals see an increase in their average BMI of approximately 2.5 percent and an increase in the likelihood of being overweight of approximately 9.8 percentage points.
Keywords: I1; I12; J61; 330; Body Mass Index; peer effects; migration; obesity